Endovascular treatment of ophthalmic artery aneurysms: ophthalmic artery patency following flow diversion versus coil embolization. (9th September 2015) - Durst, Christopher R; Starke, Robert M; Clopton, David; Hixson, H Robert; Schmitt, Paul J; Gingras, Jean M; Ding, Dale; Liu, Kenneth C; Crowley, R Webster; Jensen, Mary E; Evans, Avery J; Gaughen, John
Abstract : Background and purpose: The Pipeline Embolization Device (PED) has been shown to effectively treat complex internal carotid artery aneurysms while maintaining patency of covered side branches. The purpose of this retrospective matched cohort study is to evaluate the effect of flow diversion on the patency of the ophthalmic artery when treating ophthalmic artery aneurysms. Methods: A retrospective review of our prospectively collected institutional database identified 19 ophthalmic artery aneurysms treated with a PED. These were matched according to aneurysm diameter in a 1:2 fashion to ophthalmic artery aneurysms treated via coil embolization, although it is important to note that there was a statistically significance difference in the neck diameter between the two groups (p=0.045). Clinical and angiographic outcomes were recorded and analyzed. Results: On follow-up angiography, decreased flow through the ophthalmic artery was observed in 26% of the PED cohort and 0% of the coil embolization cohort (p=0.003). No ophthalmologic complications were noted in either cohort. Complete occlusion at 12 months was more common following PED treatment than coil embolization (74% vs 47%; p=0.089), although lower than reported in previous trials. This may be due to inflow into the ophthalmic artery keeping the aneurysm patent. Retreatments were more common following coil embolization than PED (24% vs 11%), but this was not significant (p=0.304). Permanent morbidity rates were not significantly different between the PED (11%) and coil embolization (3%) cohorts (p=0.255). Conclusions: Our results suggest that ophthalmic artery aneurysms may be adequately and safely treated with either the PED or coil embolization. However, treatment with the PED carries a higher risk of impeding flow to the ophthalmic artery, although this did not result in clinical sequelae in the current study.